ANALYSIS OF ELEMENTS OF GAME BREAKS IN FOOTBALL - Miroslav Radoman; Miroslav Smajić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Research was performed on the sample of 64 matches of the World Cup FIFA World Cup Germany 2006 and 128 results of matches classified in three wholes, according to the results: victory, defeat and draw. Analysis was carried out in relation to the element of game break during a match. The basic aim of the research was to carry out the analysis of differences in frequency of game breaks during a match. On the basis of the obtained results and their interpretation, the following conclusions may proceed: • Analysis of game breaks inferred to the fact that disqualification of a player (red card), then total number of offside, and much lower number of own goals affect the result of a match significantly; • This leads to a conclusion that the winning teams achieved lower number of public warnings (yellow cards) and disqualification of players (red cards), which means that teams were psycho-physically and technique-tactically were prepared to prevent an opponent in the defense phase from organizing an attack and scoring a goal; Based on the above we may define the basic characteristics of games of the winning teams, teams who ended their matches in a draw, and defeated teams